Sex differences in the impact of controlling nutritional status score on diabetic retinopathy: findings of 2003–2018 National Health and Nutrition Examination Survey - Han, Yu-Nan; Li, Shui-Ping; Wang, Yong-Xiang; Xiao, Zui-Xuan; Li, Lin (Frontiers in Nutrition, 2025)
BackgroundNutritional status plays a crucial role in the progression of diabetes complications. This study assessed sex differences in Controlled Nutritional Status (CONUT) score and diabetic retinopathy (DR).MethodsClinical data between 2003 and 2018 were retrieved from the National Health Nutritional Examination Survey (NHANES) database. The association of CONUT score with DR was analyzed by multivariate weighted logistic regression with restricted cubic splines (RCS). The impact of CONUT scores on DR outcomes in male and female patients was evaluated by subgroup analyses and interaction tests.ResultsA total of 3,762 participants were included in this study. After adjusting for all covariates, a higher CONUT score was positively associated with DR risk in women (OR = 1.88, 95% CI: 1.13–3.15), while no significant association between CONUT score and DR was observed in male participants and the overall participant population. In addition, RCS regression showed a linear positive correlation between CONUT score and DR risk in women (P-Nonlinear: 0.722). Subgroup analyses revealed a significant positive association of higher CONUT scores with DR risk in older female patients with diabetes, alcohol use, smoking history, hypertension, and hyperlipidemia.ConclusionThere is a sex difference in the link between higher CONUT scores and the prevalence of DR. Specifically, these findings highlight the importance of personalized nutritional intervention in women at high risk for DR.